Microglia-Derived Insulin-like Growth Factor 1 Is Critical for Neurodevelopment - Dominika Rusin; Lejla Vahl Becirovic; Gabriela Lyszczarz; Martin Krueger; Anouk Benmamar-Badel; Cecilie Vad Mathiesen; Eydís Sigurðardóttir Schiöth; Kate Lykke Lambertsen; Agnieszka Wlodarczyk (Cells, 2024)
Insulin-like growth factor 1 (IGF-1) is a peptide hormone essential for the proper development and growth of the organism, as a complete knockout of Igf1 in mice is lethal, causing microcephaly, growth retardation and the defective development of organs. In the central nervous system, neurons and glia have been reported to express Igf1, but their relative importance for postnatal development has not yet been fully defined. In order to address this, here, we obtained mice with a microglia-specific inducible conditional knockout of Igf1. We show that the deficiency in microglial Igf1, starting in the first postnatal week, leads to body and brain growth retardation, severely impaired myelination, changes in microglia numbers, and behavioral abnormalities. These results emphasize the importance of microglial-derived Igf1 for brain development and function and open new perspectives for the investigation of the role of microglial-Igf1 in neurological diseases.